Targeting heptad repeats and fusion peptide: nanoparticle vaccine elicits mucosal immune response against SARS-CoV-2 variants - Liang, Chaofeng; Li, Rong; Pu, Zeyu; Chen, Ran; Li, Yuzhuang; Chen, Siqi; Feng, Jinzhu; Liu, Jie; Bai, Yuteng; Qin, Xuewen; Xie, Chengjie; Zhang, Yixin; et al. (Journal of nanobiotechnology, 2025)
The emergence of SARS-CoV-2 variants has underscored the urgent need for innovative vaccine strategies that provide robust and enduring protection against diverse strains. Our study introduces the FP-HR5 nanoparticle vaccine, designed to target the highly conserved S2 subunit of the spike protein, including the fusion peptide (FP) and heptad repeats (HR1 and HR2), using a 24-mer Helicobacter pylori ferritin platform. Administered intranasally, the FP-HR5-NP vaccine elicits robust systemic and mucosal immune responses in vivo, generating high titers of FP- and HR5-specific IgG antibodies. Notably, intranasal immunization resulted in elevated levels of secretory IgA and IgG in bronchoalveolar lavage fluid (BALF) and stimulated T-cell immune responses, significantly increasing resident memory B cells (B ) and resident memory T cells (T ) in the lungs. In hACE2 transgenic mice, three doses of FP-HR5-NP conferred substantial protection against Delta and Omicron variant challenges, with undetectable viral RNA levels in the lungs and no pathological changes observed. Overall, the FP-HR5-NP vaccine triggers comprehensive humoral and cellular immune responses at the mucosa, providing broad defense against SARS-CoV-2 variants and positioning it as a promising candidate for a universal COVID-19 vaccine solution.